Cashless Policy And Commercial Banks’ Profitabilty In Nigeria - Akara, Chisom Kenneth; Asekome, Mike Ozemhoka (Advances in Social Sciences Research Journal, 2018)
The study examines the effects of the adoption of cashless policy on the profitability performance of commercial banks in Nigeria. By using ATM and POS as proxy for the adoption of cashless policy and ROA and ROE as proxy for profitability and using the Ordinary least Square multiple regression analysis, the study reveals that there is a high positive correlation between the adoption of cashless policy and commercial bank profitability in Nigeria. The multiple regression analysis also revealed that the use of cashless policy instruments particularly ATMs and POS increases the ROA and ROE of the banks. It is therefore recommended that the cashless policy should be strengthened and all bottle necks like poor power supply and all loopholes that could lead to fraudulent exposure be tactically proactively tackled.